2010
DOI: 10.1039/b927587h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polar organic vapors on surface potential of Au nanoparticle aggregates probed by surface-enhanced Raman scattering of 2,6-dimethylphenylisocyanide

Abstract: We demonstrate by means of surface-enhanced Raman scattering of 2,6-dimethylphenylisocyanide that the surface potential of Au nanoparticle aggregates changes upon contact with polar organic vapors such as acetone and ammonia by as much as +0.16 and -0.56 V, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 16 publications
0
19
1
Order By: Relevance
“…On the other hand, the cyclovoltammograms suggested that even a full monolayer of 2,6-DMPI does not protect platinum nanoaggregates completely from environmental chemicals. 19 This suggests that sodium and perchlorate ions can approach the electrode surface like specifically adsorbed ions, and thus the NC group of 2,6-DMPI can be understood to reside in an electric double layer even in a very dilute electrolyte solution. The NC stretching band should then be affected by the Stark effect.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the cyclovoltammograms suggested that even a full monolayer of 2,6-DMPI does not protect platinum nanoaggregates completely from environmental chemicals. 19 This suggests that sodium and perchlorate ions can approach the electrode surface like specifically adsorbed ions, and thus the NC group of 2,6-DMPI can be understood to reside in an electric double layer even in a very dilute electrolyte solution. The NC stretching band should then be affected by the Stark effect.…”
Section: Resultsmentioning
confidence: 99%
“…This is understood as a consequence of the fact that even a full monolayer of 2,6-DMPI does not protect platinum nanoaggregates completely from environmental chemicals. 19 In a separate potential-dependent SERS in electrochemical environments, the NC group of 2,6-DMPI is concluded to be located within an electric double layer even in a very dilute electrolytic solution. A part of the NC peak shift observed in this work, not only in the ambient vapor but also in the electrochemical environment, is thus assumed to arise from the Stark effect, [22][23][24][25][26][27] although the major part is due to the inductive charge transfer effect from/to platinum.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations